Review Paper On Image Inpainting Techniques - Santosh, Anushree; Vinod, P.R; Jyothirmayi, Devi C (International Journal of Computer Sciences and Engineering, 2021)
The process of reimposing the missing pixels from the flawed image and remove unwanted object is referred as Image inpainting. The most prominent purpose of the inpainting algorithm is to put back distorted and unpleasant regions and fill holes using natural method. Some common application of this technique includes remove unwanted object, restoring photos, photo retouching, or remove unwanted text, logo, stamps, copyright from the images. Based on the background information, image inpainting restore the damage part of the image by filling missing or corrupted data in the image. The restored image, which is produced as the result of applying inpainting technique will provide more realistic and more pleasant than compared to the original image. The attempt of recovering scene details blocked by visible parts is called disocclusion, which is viewed as an important part in image and depth inpainting. Holes are the occluded and impaired parts which is to be restored in an image. Hierarchical super-resolution-based, diffusion based, hybrid inpainting, texture synthesis based and exemplar-based method are used for inpainting. This paper gives brief review of the existing image inpainting approaches. This paper presents a brief survey of different image inpainting techniques and provides a relative comparison between these techniques for inpainting.